Knowledge, attitudes, and practices regarding the postoperative management and TSH suppression therapy among patients with thyroid cancer - Wu, Yongkang; Zhang, Zhi; Qin, Wenyi; Chen, Weijie; Xu, Tuo (Frontiers in Oncology, 2025)
BackgroundPatient adherence to thyroid-stimulating hormone (TSH) suppression therapy is crucial for optimizing prognosis.MethodsThis study aimed to examine the knowledge, attitude, and practice (KAP) toward TSH suppression therapy among patients. This cross-sectional study was conducted at our Hospital between March 2023 and October 2023 and included patients receiving TSH suppression therapy. A self-designed questionnaire was employed to collect their demographic characteristics and KAP. The analysis included 528 valid questionnaires.ResultsThe mean knowledge, attitude, and practice scores were 11.66 ± 5.82 (possible range: 0-22), 33.31 ± 4.97 (possible range: 0-40), and 24.46 ± 3.46 (possible range: 0-34), respectively, indicating poor knowledge, favorable attitudes, and moderate practice. The knowledge scores were correlated to the attitude (r=0.399, P<0.001) and practice (r=0.401, P<0.001) scores, while the attitude scores were correlated to the practice scores (r=0.512, P<0.001). The structural equation modeling revealed that knowledge directly influenced attitude (β=0.34, P<0.001) and practice (β=0.13, P<0.001) and indirectly influenced practice through attitude (β=0.10, P<0.001).ConclusionsPatients receiving TSH suppression therapy in Zhanjiang demonstrated poor knowledge, favorable attitudes, and moderate practices toward TSH suppression therapy.